Thanks for Watching An Anthropological Study of Video Sharing on YouTube - Lange, Patricia (University Press of Colorado, 2019)
YouTube hosts one billion visitors monthly and sees more than 400 hours of video uploaded every minute. In "Thanks for Watching," Patricia Lange offers an anthropological perspective on this heavily mediated social environment, demonstrating how core concepts from anthropology-participant-observation, reciprocity, and community-apply to sociality on YouTube and how to reconceptualize and update these concepts for video-sharing cultures.Drawing on 152 interviews with YouTube participants at gatherings throughout the United States, content analyses of more than 300 videos, observations of interactions on and off the site, and participant-observation (in which a researcher becomes part of the community she examines), Lange provides new insight into patterns of digital migration, YouTube's influence on interactions even off-site, and how the loss of control over image makes users feel posthuman.